Malaria at Parturition in Nigeria: Current Status and Delivery Outcome - Olugbenga A. Mokuolu; Catherine O. Falade; Adeola A. Orogade; Henrietta U. Okafor; Olanrewaju T. Adedoyin; Tagbo A. Oguonu; Hannah O. Dada-Adegbola; O. A. Oguntayo; Samuel K. Ernest; Davidson H. Hamer; Michael V. Callahan (Hindawi Limited, 2009)
Background. To evaluate the current status of malaria at parturition and its impact on delivery outcome in Nigeria. Methods. A total of 2500 mother-neonate pairs were enrolled at 4 sites over a 12-month period. Maternal and placental blood smears for malaria parasitaemia and haematocrit were determined. Results. Of the 2500 subjects enrolled, 625 were excluded from analysis because of breach in study protocol. The mean age of the remaining 1875 mothers was 29.0 ± 5.1 years. The prevalence of parasitaemia was 17% and 14% in the peripheral blood and placenta of the parturient women, respectively. Peripheral blood parasitaemia was negatively associated with increasing parity (P<.0001). Maternal age <20 years was significantly associated with both peripheral blood and placental parasitaemia. After adjusting for covariates only age <20 years was associated with placental parasitaemia. Peripheral blood parasitaemia in the women was associated with anaemia (PCV ≤30%) lower mean hematocrit (P<.0001). lower mean birth weight (P<.001) and a higher proportion of low birth weight babies (LBW), (P=.025). Conclusion. In Nigeria, maternal age <20 years was the most important predisposing factor to malaria at parturition. The main impacts on pregnancy outcome were a twofold increase in rate of maternal anaemia and higher prevalence of LBW.